A study of psycho-social background of children placed in remand home - Sathe, Pradnya P.; Kotnis, Shubhalaxmi D.; Mangulikar, S. K. (International Journal Of Community Medicine And Public Health, 2017)
Background: Children are one of the most vulnerable groups of societies and are at risk of many social evils. They should be identified and provided protective environment and loving care for their adequate growth and development. The aim of the study was to know psycho-social background of children in remand home. Methods: The study was carried out in Remand home Solapur which is run by Government. Based on the pilot study, 200 children were included in the study. They were interviewed regarding their personal and family background. If necessary data from remand home registers, parents, social workers and teachers were taken. Chi square test and T-test for difference between two proportions was used for the statistical analysis. Results: Out of 200 children, 78 were delinquents and 122 were non-delinquents. 144 were boys and 56 were girls. Most common reason of admission was financial constraints among non-delinquents and theft among delinquents. 12-18 yrs. old children were more involved in delinquency. Restrained relations with parents and family size played an important role in delinquency. Conclusions: Out of total 200 children, delinquency was found in 39% more in boys and 12-18 yrs. age group. Delinquency was more in children with restrained familial relations. School dropout rate was more in non-delinquents and addiction was more in delinquents.